2005
DOI: 10.1002/dmrr.541
|View full text |Cite
|
Sign up to set email alerts
|

Unmyelinated fiber sensory neuropathy differs in type 1 and type 2 diabetes

Abstract: The more severe molecular, functional and morphometric abnormalities of nociceptive C-fibers in type 1 insulinopenic rats compared to type 2 hyperinsulinemic rats suggest that impaired insulin action may play a more important pathogenetic role than hyperglycemia per se.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
86
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(95 citation statements)
references
References 57 publications
8
86
0
Order By: Relevance
“…Many reports demonstrated that CGRPergic nerves were highly dependent on neurotrophic support provided by insulin. 26,27 Based on these evidences, decrease in the density of CGRPergic nerve fibers in FDR mesenteric arteries might be involved in impaired insulin action on CGRPergic nerves, although further investigations are needed to test this mechanism. In contrast, previous reports demonstrate that sympathetic nerve terminals were less susceptible to insulin resistance than other organs in insulin-resistant model.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports demonstrated that CGRPergic nerves were highly dependent on neurotrophic support provided by insulin. 26,27 Based on these evidences, decrease in the density of CGRPergic nerve fibers in FDR mesenteric arteries might be involved in impaired insulin action on CGRPergic nerves, although further investigations are needed to test this mechanism. In contrast, previous reports demonstrate that sympathetic nerve terminals were less susceptible to insulin resistance than other organs in insulin-resistant model.…”
Section: Discussionmentioning
confidence: 99%
“…Thermal plantar test. Latencies of hind paw withdrawal to thermal stimulation (42°C; 152 mW/cm 2 ) were used as measures of thermal hyperalgesia and were measured at 4 and 7 months using a UGO Biological Research apparatus (Comerio, Italy) (11,12). The time from heat source activation to the animal's self-withdrawal in seconds was measured six times in alternating hind paws.…”
Section: Methodsmentioning
confidence: 99%
“…Photographs were enlarged 10,000 times, scanned, and downloaded to a computerized image analysis system (Image-1; Universal Imaging, West Chester, PA). The following morphometric parameters of unmyelinated fibers were obtained: unmyelinated fiber number, fiber density (n/mm 2 ), mean fiber size (m 2 ), axon numbers per Schwann cell unit, and the frequencies of type 2 Schwann cell/axon relationship, collagen pockets, denervated Schwann cell profiles, and regenerating C-fibers (12). Identification and morphometry of substance P and calcitonin generelated peptide-positive DRG neurons.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations